Development of a bioactive glass fiber reinforced starch-polycaprolactone composite - Jukola, H. (2008)
For bone regeneration and repair, combinations of different materials are often needed. Biodegradable polymers are often combined with osteoconductive materials, such as bioactive glass (BaG), which can also improve the mechanical properties of the composite. The aim of this work was to develop and characterize BaG fiber reinforced starch–poly-ecaprolactone (SPCL) composite. Sheets of SPCL (30/70 wt %) were produced using singlescrew extrusion. They were then cut and compression-molded in layers with BaG fibers to form composite structures with different combinations. Mechanical and degradation properties of the composites were studied. The actual amount of BaG in the composites was determined using combustion tests. Initial mechanical properties of the reinforced composites were at least 50% better than the properties of the nonreinforced specimens. However, the mechanical properties of the composites after 2 weeks of hydrolysis were comparable to those of the nonreinforced samples. During the 6 weeks hydrolysis the mass of the composites had decreased only by about 5%. The amount of glass in the composites remained as initial for the 6-week period of hydrolysis. In conclusion, it is possible to enhance initial mechanical properties of SPCL by reinforcing it with BaG fibers. However, mechanical properties of the composites are typical for bone fillers and strength properties need to be further improved for allowing more demanding bone applications.